ANALISIS YURIDIS ANAK SEBAGAI PELAKU TINDAK PIDANA PERJUDIAN ONLINE (STUDI KASUS DI WILAYAH HUKUM POLRESTABES MEDAN) - Tevin, Dini Rizki (Universitas Harapan Medan, 2023)
Gambling conducted online on the internet is regulated in Article 27 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 or hereinafter referred to as the Electronic Information and Transaction Law. The threat to this offense is regulated in Article 45 paragraph (2) of the Electronic Information and Transaction Law. The formulation of the problem in this thesis is how the form of law enforcement by the Medan police station against children as online gambling offenders, what are the factors that cause children to commit online gambling crimes in the Medan police jurisdiction, how are the efforts of the Medan police station in tackling children as online gambling offenders. The writing of this thesis uses empirical legal research methods, commonly referred to as field research or field research, which is a type of research oriented towards collecting empirical data in the field, and analyzed qualitatively. The conclusion of the discussion is that in general, minors who are involved in criminal acts such as online gambling in the Medan Police jurisdiction are due to peer factors, environmental factors, and lack of parental supervision, the form of law enforcement by Medan Police against children as online gambling offenders is by inviting the child's parents and involving bapas, In the preparation of the Juvenile Criminal Justice System Law No. 11 of 2012 adheres to the principle of equality before the law, as well as if the perpetrator is a child, then the child must also be responsible for his actions, no exception for children who commit gambling, countermeasures against cases of children as online gambling offenders carried out by the police, namely preventive, repressive, persuasive, and curative efforts.